Islamic banking industry in fintech ecosystem: issues and challenges / Hasmah Laili Jamalurus - Jamalurus, Hasmah Laili (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
Financial Technology or 'FinTech' implies the utilization of technology and mobile devices for information access to transaction notifications, bank accounts and credits, debit alerts with short message services, or other applications that inextricably link customers to banking institutions (Stewart & Jürjens, 2018). The emergence of FinTech started after the financial crisis in 2007/2008 due to decrease in customer trust towards the traditional banking system (Breidbach et al., 2019). The application of Fintech in Islamic banks or companies is permissible, providing it complies with the principles of Shariah. Embracing such technological advancements will improve Islamic banking services, preserve customers' digital security and provide them with easy access to digital transactions. As the percentage of the unbanked population remained high in OIC member countries, Islamic Fintech is considered a solution in providing access to banking services. Despite that, the demand for Islamic Fintech will increase tremendously with the growing population of the young and tech-savvy Muslim generation. The position of a world leader in Islamic finance gives advantages to the Islamic banking industry in Malaysia to explore more mechanisms to support the digital transformation, including FinTech. The supportive regulatory environment, well-established capacity building, and readiness of the existing or new customers are among the substantial factors contributing to the growth of Islamic Fintech application in the Islamic banking industry.